Rancang Bangun Penilaian Kinerja Sales Berbasis Web Pada PT. World Innovative Telecommunication - Ari Tri Anggoro; Hany Maria Valentine; Sharyanto Sharyanto (Eksplorasi Teknologi Enterprise & Sistem Informasi (EKSTENSI), 2023)
PT. World Innovative Telecommunication is a company engaged in the retail sector. Especially in smartphone sales. Currently performance appraisal is still done manually where the manager takes data directly and then evaluates the data taken by manual calculation so that human errors often occur such as calculation errors in each calculation can occur around 5-9 times errors and data storage does not have back up so prone to data loss. From the description of the problems that occurred, it was designed and built a Web-Based Sales Performance Assessment Information System at PT. World Innovative Telecommunication which is expected to solve existing problems. For analysis and design using the Unified Modeling Language (UML). Web-Based Sales Performance Assessment Information System uses the programming language PHP and MySQL as its database.